Earthworms The Ecological Engineers of Soil - Ray, Sajal (IntechOpen, 2018)
This book in two sections represents the current trend of research in ecology and biology of earthworms. In section "Ecology and Diversity" the authors reported the ecological and geographical uniqueness and diversity of earthworms in different environmental terrains of Siberia and Mexico. Functional interaction between earthworms and soil nematodes was elucidated with reference to vermicomposting and agricultural systems. Importance of digital library was highlighted for inventorization and taxonomical identification of earthworms. In section "Vermicomposting" the importance of maintaining pure cultures was discussed from the viewpoint of growth rate and the reproduction of composting species. This section includes article describing the management-related issues like roles of physicochemical parameters of soil and feed mixture on growth and reproduction of commercially important species of earthworm.